Foreign language anxiety research in System between 2004 and 2023: looking back and looking forward - Yu, Qiangfu (Frontiers in Psychology, 2024)
With the deepening of the research on emotional factors, foreign language anxiety (FLA) has become the focus of researchers in the field of foreign language learning (FLL) and teaching. This paper aims to provide an overview of the historical trajectory of FLA research that has been published in System between 2004 and 2023. While examining the retrieved 49 studies, focus has been laid on the methodologies including research instruments, methods, participants, major themes and key findings of FLA research. Although almost all of the studies employed quantitative and mix-methods methodologies, questionnaires and semi-structured interviews were the most preferred research methods. FL learners from 21 countries/ regions were represented, but a significant number of the studies came from China, Japan and Iran.And an overwhelming majority of the studies focused on FLA among the learners learning English as a foreign language (EFL). The review concluded with some research lacunae and possible directions for future research on FLA.